2006
DOI: 10.1111/j.1475-097x.2007.00708.x
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric evaluation of upper extremities in 250 healthy persons

Abstract: Water displacement as used in this study is a highly reliable technique for volume measurement of upper extremities. This technique was applied to gather normative data for upper extremity volumes. We suggest that this technique can be used in daily clinical practice for the evaluation of upper extremity oedema or atrophy caused by various diseases as well as for volume monitoring. Prediction formulas can be used to define abnormal swelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…25 While this criteria has been accepted and supported for other tools used in the diagnosis of swelling, 25 others have suggested that two standard deviation above the mean may be more appropriate. 26 If a mean plus two standard deviation cut-off were to be adopted, our data indicate that for volume these would be 275 mL and 115 mL for the dominant and nondominant arm, respectively, when measured by perometry. The respective values for truncated cone measurements of volume would be 200 mL and 150 mL.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…25 While this criteria has been accepted and supported for other tools used in the diagnosis of swelling, 25 others have suggested that two standard deviation above the mean may be more appropriate. 26 If a mean plus two standard deviation cut-off were to be adopted, our data indicate that for volume these would be 275 mL and 115 mL for the dominant and nondominant arm, respectively, when measured by perometry. The respective values for truncated cone measurements of volume would be 200 mL and 150 mL.…”
Section: Discussionmentioning
confidence: 98%
“…This may not be the best way to determine which hand is actually dominant, as it has been suggested that the Edinburgh Handedness Inventory is a more valid method to determine handedness. 26 Clinically, however, a patient's limb dominance is usually self-determined, as was done for this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigations have shown that the measurement of hand (Eccles 1956;Farrell et al 2003), arm (Engler and Sweat 1962;Gebruers et al 2007;Sagen et al 2005;Taylor et al 2006) and foot (Goldie et al 1974) edema using volumetry is highly reliable. For example, Moholkar and Fenelon (2001) examined diurnal variation in edema of the feet and ankles by taking four water displacement measurements across a 9-h period in 20 adults restricted to bed rest.…”
Section: Introductionmentioning
confidence: 96%
“…11,12,19 Secondary thresholds of two standard deviations were also determined. 20 Intra-rater reliability and normal fluctuation of BIS ratios were determined with intraclass correlation coefficients (ICC (1,1) ) from data collected on two occasions seven days apart. Standard error of the measurement (SEM = SD 1st test O1-ICC) and minimal detectable change (MDC = 1.96 O2 SEM) were determined for each arm segment and the hand.…”
Section: Discussionmentioning
confidence: 99%